1999
DOI: 10.1891/0886-6708.14.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Aggressive Women: The Effects of Gender, Socioeconomic Status, and Level of Aggression

Abstract: Research finds gender differences in aggression and suggests that female violence is viewed differently from male violence. Participants were 94 female and 38 male students from a mid-size public university in the Southeast. Participants read a mock trial and answered questions about their attitudes concerning an aggressor in the scenario. The study was a 2 (male or female) by 2 (high socioeconomic status or low socioeconomic status) by 2 (verbal aggression or physical aggression) between-subjects factorial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…This was true regardless of the physical attractiveness of the characters, and is therefore not merely a case of interpreting questionable moral behavior in a positive light due to a halo effect. This effect of protagonist aggression on the perception of that protagonist’s worth as a role model seems to run counter to past findings indicating disapproval of aggression in general, particularly when undertaken by women (Barber et al 1999). The observed perception may reflect the success achieved through aggression—individuals who achieve goals or who win may be perceived as more desirable role models regardless of whether they use aggression.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This was true regardless of the physical attractiveness of the characters, and is therefore not merely a case of interpreting questionable moral behavior in a positive light due to a halo effect. This effect of protagonist aggression on the perception of that protagonist’s worth as a role model seems to run counter to past findings indicating disapproval of aggression in general, particularly when undertaken by women (Barber et al 1999). The observed perception may reflect the success achieved through aggression—individuals who achieve goals or who win may be perceived as more desirable role models regardless of whether they use aggression.…”
Section: Discussioncontrasting
confidence: 97%
“…Although aggression, especially by women, is often seen in a negative light, this perception is not uniform (Barber et al 1999; Brown and Sumner 2006). Past research has demonstrated that women’s aggression results in greater opprobrium than identical acts of aggression performed by men, but that bias is eliminated among individuals who endorse more egalitarian gender norms (Barber et al 1999; Brown and Sumner 2006). Furthermore, when individuals show anger, an emotion often associated with and predictive of aggression, they are perceived as more competent and more worthy of elevated status (Tiedens 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These norms generally prohibit women from using defiance, resistance, aggression, or violence against their male partners (Dasgupta 2002;Renzetti 1994). Studies show that females who target their male partners for physical aggression encounter more negative judgments than females who use verbal aggression (Barber et al 1999). In addition, females who use high resistance to avoid stranger or acquaintance rape receive harsher judgments than females who use moderate resistance (Branscombe and Weir 1992).…”
mentioning
confidence: 99%
“…Therefore, we used threat scenarios. Although there might be differences between action tendencies and actual reactions in times of threats and danger, research has indicated that scenarios have high predictive validity (e.g., Barber, Foley, & Jones, 1999;Erber, Szuchman, & Prager, 2001), and that they can elicit considerable emotional and physiological reactions (e.g., Bernat, Calhoun, & Adams, 1999;Conklin, Tiffany, & Vrana, 2000). Second, people's reactions to threats are influenced not only by situational features or by their personality but also by the presence of other people around them.…”
Section: Discussionmentioning
confidence: 99%